Antibacterial Activity of Haematococcus pluvialis Crude Astaxanthin Extract - Rather, Ashaq Hussain; Singh, Surendra; Choudhary, Sameer (Journal of Drug Delivery and Therapeutics, 2021)
H. pluvialis is the potential source of natural astaxanthin, which is considered as super antioxidant. In the present investigation, astaxanthin was extracted from the encysted cells of H. pluvialis with acetone, methanol, DMSO and hexane, the crude extracts were tested for four strain (Escherichia coli, Salmonella typhi, Vibrio cholera and Staphylococcus aureus)of bacteria for the antibacterial activity. Highest antibacterial activity was observed as 10.2 ±0.20 mm extracted with acetone on Escherichia coli while as least antibacterial activity was found as6.1±0.0 mm extracted with hexane on Vibrio cholera. Keywords: Haematoccoccus pluvialis; Astaxanthin; Antibacterial.